Get Vaccinated! and Get Tested! Developing Primary and Secondary Cervical Cancer Prevention Videos for a Haitian Kreyòl-Speaking Audience. Issue 5 (3rd May 2016) - Frett, Brigitte; Aquino, Myra; Fatil, Marie; Seay, Julia; Trevil, Dinah; Fièvre, Michèle Jessica; Kobetz, Erin
Abstract : Although routine screening reduces cervical cancer rates between 60% and 90%, thousands of women worldwide are diagnosed with the disease on an annual basis because of inadequate screening. Haitian women in South Florida experience a disproportionate burden of cervical cancer, with disease rates 4 times higher than the average for women in Miami. An ongoing community-based participatory research initiative to assess and reduce this burden has revealed that a complex interplay of factors contributes to a lack of access to screening in this community, including socioeconomics, language barriers, and traditional understandings of health and disease. In an effort to address some of these barriers and encourage uptake of primary and secondary cervical cancer prevention strategies, 2 videos on cervical cancer prevention were created using a community-based participatory research framework. The video screenplays were created by a Haitian screenwriter using evidence-based medical information provided by academic researchers. The films feature Haitian actors speaking a Haitian Kreyòl dialogue with a storyline portraying friends and family discussing human papillomavirus disease and vaccination, Papanicolaou testing, and cervical cancer. Focus groups held with Haitian women in South Florida suggested that the films are engaging; feature relatable characters; and impact knowledge about human papillomavirus, cervical cancer development, and current prevention recommendations.